Pregnancy and HIV infection. Experience in the Hospital A. Loayza - Mere, Juan (2015)
OBJECTIVE: To evaluate the first experiences of HIV+ pregnant women who delivered at the Loayza General Hospital in 1996 and 1997. MATERIAL: Retrospective stay of 20 pregnant women HIV+. RESULTY: The incidence was 0,18% and increased from one year to anotherin about 50% (0,15% in 1996 to 0,22% in 1997). Four were classified as AIDS and sixteen as HIV+. Fourteen mothers were bettween 21 and 30 years old (70%) and four between 16 and 20 years (20%). Single mothers represent 35%. Secondary students or some with any year of high school total 95%, 20% of them began sexual activity before 15 years, 45% were pregnancy the first time. Twelve pregnant women (60%) bad an adequate prenatal care, they received zidovudine (AZT) during 10,7 weeks in average, giving hirth eight of them by elective cesarean section (5 arrived to the obstetric room with complete dilatation). Three patients presented condiloma acuminata (15%). Only six quantified CD 4+ Tlymphocytes, presenting four cases levels below 200 cel/μL (2 with AIDS and prenatal care). There were no preterm deliveries nor puerperal complications. All 20 newborns were between 37 and 41 weeks of gestational age, with 15% of them (3) small for gestational age. Up to october 1998, 2 children (10%) were seroreverted (2 motbers with prenatal care who received AZT).